2014
DOI: 10.1038/nrneph.2014.103
|View full text |Cite
|
Sign up to set email alerts
|

Pre-eclampsia part 2: prediction, prevention and management

Abstract: An antiangiogenic state might constitute a terminal pathway for the multiple aetiologies of pre-eclampsia, especially those resulting from placental abnormalities. The levels of angiogenic and antiangiogenic proteins in maternal blood change prior to a diagnosis of pre-eclampsia, correlate with disease severity and have prognostic value in identifying women who will develop maternal and/or perinatal complications. Potential interventions exist to ameliorate the imbalance of angiogenesis and, hence, might provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
102
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 140 publications
0
102
0
1
Order By: Relevance
“…Uteroplacental ischemia can lead to the production of anti-angiogenic factors [103113], such as sFlt-1 (soluble fms-like tyrosine kinase-1) [114117] and endoglin [69,118], which can induce endothelial dysfunction and predispose to preeclampsia or an anti-angiogenic state [57,119129]. In addition, an excess production of trophoblast debris can result in exaggerated intravascular inflammation and endothelial cell dysfunction [130134].…”
Section: Commentmentioning
confidence: 99%
“…Uteroplacental ischemia can lead to the production of anti-angiogenic factors [103113], such as sFlt-1 (soluble fms-like tyrosine kinase-1) [114117] and endoglin [69,118], which can induce endothelial dysfunction and predispose to preeclampsia or an anti-angiogenic state [57,119129]. In addition, an excess production of trophoblast debris can result in exaggerated intravascular inflammation and endothelial cell dysfunction [130134].…”
Section: Commentmentioning
confidence: 99%
“…There is a growing body of evidence indicating that an imbalance in maternal plasma concentrations of angiogenic and anti-angiogenic factors is characteristic of a substantial fraction of women who have or will develop preeclampsia [44, 97107, 110, 111, 130–168], fetal death [114, 115, 169173], SGA [64, 102104, 117, 173178], massive perivillous fibrin deposition [115, 178], twin-to-twin transfusion syndrome [118, 179, 180], and mirror syndrome [181]. We have also found significant differences in angiogenic marker distributions among uncomplicated pregnancies and those who are or will be affected by spontaneous PTL with intact membranes [112].…”
Section: Commentmentioning
confidence: 99%
“…Our group demonstrated that an imbalance in maternal plasma concentrations of the angiogenic placental growth factor (PlGF) and anti-angiogenic factors [e.g., soluble vascular endothelial growth factor receptor-1 (sVEGFR-1)] is characteristic of a large fraction of women who have or will develop preeclampsia [44, 97111]. We also found significant differences in angiogenic and anti-angiogenic factor distributions among women with uncomplicated pregnancies and those who are or will be affected by spontaneous PTL with intact membranes [112], fetal death [109, 113, 114], massive perivillous fibrin deposition [115], twin-to-twin transfusion syndrome [116], and delivery of SGA newborns [103, 117, 118].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 -12) Excessive GWG has been suggested to increase the risk of preeclampsia, and be associated with the inflammatory milieu, maternal body composition, body fat distribution, hyperlipidemia, insulin resistance, and coagulation abnormalities associated with the pathogenesis of preeclampsia. 13,14) However, the contribution of fluid retention secondary to edema has often been insufficiently considered in simple associations between total GWG and the prevalence of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%